The Essential Functions and Detection of Bisecting GlcNAc in Cell Biology - Chen, Qiushi; Tan, Zengqi; Guan, Feng; Ren, Yan (Frontiers in Chemistry, 2020)
The N-glycans of mammalian glycoproteins vary greatly in the structure, but the biological importance of this variation is nearly unknown. It is widely acknowledged that bisecting N-acetylglucosamine (GlcNAc) structure, a β1,4-linked GlcNAc attached to the core β-mannose residue, represents a special type of N-glycosylated modifications, and has been reported to involve in various biological processes, such as cell adhesion, fertilization and fetal development, neuritogenesis and tumor development. Especially, the occurrence of N-glycans with a bisecting GlcNAc modification on proteins has been proved with many implications in immune biology. Due to the essential functions of bisecting GlcNAc structures, the analytical approaches on this modification are highly required. The traditional approach previously employed for bisecting GlcNAc determination is based on the lectin recognition of Phaseolus vulgaris erythroagglutinin (PHA-E); however, the poor specificity of the binding obstacles the application of this method. With the development of Mass spectrometry (MS) in high resolution, improved sensitivity and accuracy, MS-based glycomic analysis has provided precise characterization and quantification for glycosylation modification. In this review, we first provide an overview of bisecting GlcNAc structure and its biological importance in immune tolerance, neurologic function and tumor metastasis and development, and then summarize their determination approaches by MS for performing precise function studies. This review is valuable for the readers who are interested in the importance of bisecting GlcNAc in cell biology.